Efektivitas Kelembagaan Pemerintah dalam Integrasi Pola Pengelolaan Sumber Daya Air dalam Rencana Tata Ruang Wilayah (Studi Kasus: Provinsi Jawa Tengah) - Silviani Junita; Imam Buchori (Jurnal Wilayah dan Lingkungan, 2016)
The effectiveness of integrating water resources management into spatial planning (RTRW) can be achieved if there is a harmonious coordination between central government and local government. This research aims to analyze the role of and coordinating pattern of inter-sectoral institutions related to water resource planning and management in spatial planning. The research is conducted by using qualitative approach through the analysis of the role of and coordination in inter-sectoral institutions and the effectiveness of the successful integration of water resources management in spatial planning. The findings show that the integration of water resources management pattern in the spatial planning is ineffective indicated by the ineffectiveness of government institution as the policy maker and the lack of coordination between institutions regarding the content of water resource management in spatial planning. Therefore, it is necessary to make a coordination forum to accommodate the interests of water resources and spatial planning.